Challenges to select suitable habitats and demonstrate 'additionality' in Blue Carbon projects: A seagrass case study. (1st November 2020) - Lafratta, A.; Serrano, O.; Masqué, P.; Mateo, M.A.; Fernandes, M.; Gaylard, S.; Lavery, P.S.
Abstract: Seagrass restoration has been suggested as a Blue Carbon (BC) strategy for climate change mitigation. For Nationally Determined Contributions (NDC) and carbon crediting schemes, BC projects need to demonstrate 'additionality', that is enhanced CO2 sequestration and/or avoided greenhouse gas emissions following management actions. This typically requires determining soil carbon accumulation rates (CAR), which is often done using radionuclides or surface elevation tables to estimate sedimentation rates. Here we undertook a case study, using 210 Pb and 14 C dating, to detect possible changes in Corg stocks and CAR following the loss and partial recovery of Posidonia seagrass meadows in South Australia since 1980–90s. The 210 Pb data revealed a lack of accumulation of excess 210 Pb in most sites, suggesting negligible accumulation of sediments, intense mixing of the upper layers, or accumulation of reworked sediments, precluding the estimation of reliable CAR at decadal time scales. This limitation was also encountered with 14 C. The inability to compare sites over analogous periods of time prevented quantifying differences in soil Corg sequestration, thereby to demonstrate additionality. The lack of significant differences in soil Corg stocks among sites which never suffered seagrass loss, those showing recovery and those with no recovery (5.7 ± 1.2, 4.5 ± 0.7 and 3.3 ± 0.3 kg Corg m - 2 within the top meter, respectively) also precluded estimates of soil Corg gains or losses. Our findings demonstrate that, while 210 Pb and 14 C provide important information on sediment deposition dynamics, it is not straightforward to demonstrate additionality using radionuclides in low depositional seagrass habitats exposed to hydrodynamic energy, features which may be encountered in seagrass sites. We provide insights for the selection of suitable habitats for seagrass BC projects, suggest possible alternative methods for estimating additionality, and discuss the implications of the findings for the implementation of seagrass BC strategies to mitigate greenhouse gas emissions. Graphical abstract: Image 1 Highlights: Demonstrating Corg gains and losses in BC projects constrained by methods and hydrodynamics. Determining CARs using radionuclides may be impossible in some seagrass sites. Carefully site selection should precede the implementation of seagrass BC projects. Depositional environments protected from hydrodynamic energy are more suitable for BC projects.